Halal Certification Management Procedure for Cosmetic Products in Indonesia After Government Regulation Number 31 of 2019: Prosedur Pengelolaan Sertifikasi Halal pada Produk Kosmetik Pasca Peraturan Pemerintah Nomor 31 Tahun 2019 - Alam, Azhar; Yunie Samhuri, Refita (El-Qist: Journal of Islamic Economics and Business (JIEB), 2021)
Abstract: In ensuring the halalness of a product, the Indonesian government issued Government Regulation no. 31 of 2019, following up on changes to the flow of halal certification as stated in the Halal Product Assurance Law Number 33 of 2014, which the Ministry of Religion manages, Division of the Halal Product Assurance Organizing Body (BPJPH). This study aims to reveal the differences in the management of halal certificates before and after the Halal Product Guarantee Act (UU JPH). In addition, this study also discusses the procedures carried out by LPPOM - MUI and BPJPH in the management of halal certificates for cosmetic products. This study uses a descriptive qualitative approach, with the research object being LPPOM MUI and BPJPH Banten Province. Data were obtained from interviews, literature documents. The study results indicate significant changes that occur with the emergence of the role of BPJH as the central institution authorized in the halal certification process. The management of halal certification for cosmetic products is adjusted to the tariff with categories ranging from large, medium, medium, or home industry businesses. Keywords: Cosmetics, LPPOM MUI, BPJPH, Halal Certification   Abstrak:Dalam menjamin kehalalan suatu produk, maka pemerintah Indonesia mengeluarkan Peraturan Pemerintah No. 31 Tahun 2019 menindaklanjuti perubahan alur pembuatan sertifikasi halal sebagaimana tertuang dalam Undang-Undang Jaminan Produk Halal Nomor 33 Tahun 2014 yang dikelola oleh Kementrian Agama Divisi Badan Penyelenggara Jaminan Produk Halal (BPJPH). Penelitian ini bertujuan untuk mengungkapkan perbedaan pengelolaan sertifikat halal sebelum dan sesudah adanya Undang Undang Jaminan Produk Halal (UU JPH). Selain itu penelitian ini juga membahas prosedur yang dilakukan LPPOM – MUI dan BPJPH dalam pengelolaan sertifikat halal pada produk kosmetik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan objek penelitian adalah LPPOM MUI dan BPJPH Provinsi Banten. Data diperoleh dari hasil wawancara, dokumen literatur. Hasil Penelitian menunjukkan adanya perubahan yang signifikan yang terjadi dengan munculnya peran BPJH sebagai lembaga utama yang berwenang dalam proses sertifikasi halal. Pengurusan sertifikasi halal produk kosmetik disesuaikan besaran tarifnya dengan kategori jenis mulai dari besar, menengah, sedang, atau usaha industri rumah tangga. Kata Kunci : Kosmetik, LPPOM MUI, BPJPH, Sertifikasi Halal.